2016
DOI: 10.1099/jmmcr.0.005064
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae type a as a cause of paediatric septic arthritis

Abstract: Introduction:Incidence rates of invasive Haemophilus influenzae serotype b disease have decreased significantly since the introduction of the Hib vaccine; however, the rates in indigenous populations remain disproportionately high, specifically in the paediatric population. Additionally, with the decline of type b invasive infections, there has been a rebound in the incidence of invasive infections caused by other strains of H. influenzae, particularly serotype a.Case presentation:We present a paediatric case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…These findings suggest that high Hia circulation rates in First Nations communities stimulate the development of antibodies because of an increased exposure of the population to Hia antigens. Indeed, our epidemiological studies have demonstrated that in this region, most cases of invasive Hia disease occur in First Nations [ 12 , 13 , 22 , 24 , 33 ]. Moreover, our ongoing research in First Nations communities of Northwestern Ontario identified Hia as a common cause of pediatric otitis media and found that approximately 8% of 3–5 year old children carry Hia in the nasopharynx (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that high Hia circulation rates in First Nations communities stimulate the development of antibodies because of an increased exposure of the population to Hia antigens. Indeed, our epidemiological studies have demonstrated that in this region, most cases of invasive Hia disease occur in First Nations [ 12 , 13 , 22 , 24 , 33 ]. Moreover, our ongoing research in First Nations communities of Northwestern Ontario identified Hia as a common cause of pediatric otitis media and found that approximately 8% of 3–5 year old children carry Hia in the nasopharynx (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…There are growing numbers of sporadic case reports, case series, and retrospective studies with various clinical presentations of invasive Hia infection globally. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Most of these reports show the greatest burden of invasive Hia disease in children ≤ 5 years or adults > 65 years, 32 with short-and long-term adverse outcomes exclusively in young children ≤ 5 years of age. 23,31,33 We described two cases of invasive Hia infection in children > 5 years of age who presented within a 2-month period to our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…H influenzae is strictly a human pathogen, gram-negative coccobacillus, which usually infects the upper respiratory tract and can cause serious invasive infections, especially in children younger than 5 years. [1][2][3][4][5][6][7][8] There are 6 encapsulated serotypes characterized by distinctive capsular polysaccharides (a-f), as well as 3 nonencapsulated or nontypeable strains. 2,3,7 In 1994, invasive Hif was reported to occur at frequency of 1.9 cases per 1 million children with pneumonia and meningitis being the most common presentations.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,7 In 1994, invasive Hif was reported to occur at frequency of 1.9 cases per 1 million children with pneumonia and meningitis being the most common presentations. 9 The percentage of Hif infections has declined with universal introduction of the conjugate vaccine.10 With this decline, the incidence of invasive infections caused by nontypeable or other strains of H influenzae, 5,7,11 particularly serotype f, has grown in the United States as well as other countries. [12][13][14] In the pediatric population, pneumonia and meningitis are the most common forms of severe Hif infection.…”
Section: Discussionmentioning
confidence: 99%